Cone Beam CT Evaluation of the Prevalence and Characteristics of the Retromolar Canal - Movahhedian N; Shahidi SH; Bahadori Jahromi M (Shiraz University of Medical Sciences, 2017)
Statement of problem: Retro-molar canal (RMC) is of clinical significance because of its neurovascular content, which may be at risk of damage during the surgical procedures of the area. Objectives: The aim of the present study was to evaluate the frequency and anatomic characteristics of RMC by using cone beam computed tomography (CBCT). Materials and Methods: The sample of this study consisted of 500 CBCT images (1000 sides), evaluated for the presence, type, and width of RMC. The canals were categorized into five groups based on their course as A1 (vertical), A2 (vertical with a horizontal branch), B1 (curved), B2 (curved with a horizontal branch), and C (horizontal). Results: The study showed that 57 (11.4%) subjects and 67 (6.7%) sides had RMC in which 47 (9.4 %) were unilateral and 10 (2%) were bilateral. There was no statistically significant difference between male and female individuals in the occurrence of RMC (10.2% and 12.7%, respectively) (P-value=0.387). The most common morphologic types were B1 (50.7%) and A1 (23.9%), while A2 (3%) and B2 (4.5%) were the least frequent types. The mean width of the mandibular canal and RMC were 3.51 ± 0.55 mm and 1.30 ± 0.47 mm, respectively. These dimensions were not significantly influenced by gender (P-value=0.440, 0.569, respectively). Conclusions: The results of the present investigation showed that the RMC was a common anatomic structure. Therefore, because of its clinical significance, it is highly recommended that dental practitioners consider this structure in pre-surgical evaluations of the region in order to avoid related complications.